2011
DOI: 10.1099/mic.0.044933-0
|View full text |Cite
|
Sign up to set email alerts
|

Rga is a regulator of adherence and pilus formation in Streptococcus agalactiae

Abstract: Streptococcus agalactiae is the leading cause of bacterial sepsis and meningitis in neonates and is also the causative agent of several serious infections in immunocompromised adults. S. agalactiae encounters multiple niches during an infection, suggesting that regulatory mechanisms control the expression of specific virulence factors in this bacterium. The present study describes the functional characterization of a gene from S. agalactiae, designated rga, which encodes a protein with significant similarity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
(95 reference statements)
0
15
0
Order By: Relevance
“…S2 in the supplemental material). Poor expression of PI-2a in strain 2603 is likely due, at least in part, to one or both of the frameshift mutations that abrogate expression of the two regulatory proteins, RogB and Rga, that normally activate PI-2a gene transcription (3,4,29). These results indicated that pilus 2a is expressed poorly or not at all in strain 2603, so pilus 1 is the only potentially functional pilus in this strain (see below).…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…S2 in the supplemental material). Poor expression of PI-2a in strain 2603 is likely due, at least in part, to one or both of the frameshift mutations that abrogate expression of the two regulatory proteins, RogB and Rga, that normally activate PI-2a gene transcription (3,4,29). These results indicated that pilus 2a is expressed poorly or not at all in strain 2603, so pilus 1 is the only potentially functional pilus in this strain (see below).…”
Section: Resultsmentioning
confidence: 74%
“…We found a modest increase (about 2-fold) in PI-2a gene expression in 515 ⌬csrR, a csrR deletion mutant in the type Ia GBS strain 515 (unpublished data). Two RofA family proteins, RogB and Rga, were reported to be activators of PI-2a pilus expression in NEM316 (3,4,29). However, frameshift mutations are found in both rogB and rga in GBS 2603, consistent with the poor expression of the PI-2a pilus.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Transcriptional regulators such as RovS, a member of the Rgg protein family (34); Rga, a RofA-like protein (33); and the RgfA/C two-component system (1,42) have been found to modulate GBS adherence to host cells or ECM, but the molecular basis of the coordinated expression of GBS adherence factors remains incompletely understood.…”
mentioning
confidence: 99%